2021
DOI: 10.1136/archdischild-2021-322578
|View full text |Cite
|
Sign up to set email alerts
|

Association of childhood tracheomalacia with bronchiectasis: a case–control study

Abstract: ObjectiveChildren with tracheomalacia can develop chronic lower airway infection and neutrophilic inflammation. It is plausible children with tracheomalacia are at increased risk of developing bronchiectasis. We hypothesised that compared with controls, tracheomalacia in children is associated with bronchiectasis.DesignSingle-centre, case–control study.Setting and patients45 children with chest high-resolution CT (c-HRCT) confirmed bronchiectasis (cases) and enrolled in the Australian Bronchiectasis Registry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…These airway anomalies seem to be predisposed to and are closely associated with chronic recurrent airway infection and consequent inflammation. For example, a recent case-control study demonstrated that the presence of tracheomalacia (defined by European Respiratory Society as >50% expiratory reduction in the cross-sectional luminal area seen on flexible bronchoscopy) is an independent risk factor for bronchiectasis with an adjusted odds ratio of 24.4, and a 95% confidence interval (CI) of 3.4 to infinity (18).…”
Section: Aetiological Causes Of Chronic Coughmentioning
confidence: 99%
“…These airway anomalies seem to be predisposed to and are closely associated with chronic recurrent airway infection and consequent inflammation. For example, a recent case-control study demonstrated that the presence of tracheomalacia (defined by European Respiratory Society as >50% expiratory reduction in the cross-sectional luminal area seen on flexible bronchoscopy) is an independent risk factor for bronchiectasis with an adjusted odds ratio of 24.4, and a 95% confidence interval (CI) of 3.4 to infinity (18).…”
Section: Aetiological Causes Of Chronic Coughmentioning
confidence: 99%
“…Apart from bronchiectasis related to cystic fibrosis and recurrent pneumonia, there is little understanding about its etiology in pediatrics but prevalence appears to be increasing and more than 20% have no clear cause identified 3,6,7 . Diagnostic work‐up and management for these patients varies widely and it is likely these factors impact clinical outcomes as some studies have suggested reversal of disease with treatment 1,8,9 . However, little is known about risk factors for disease and better understanding of these risks might allow for targeted approaches to prevent ongoing pulmonary damage in pediatric patients who are at risk 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 Diagnostic workup and management for these patients varies widely and it is likely these factors impact clinical outcomes as some studies have suggested reversal of disease with treatment. 1,8,9 However, little is known about risk factors for disease and better understanding of these risks might allow for targeted approaches to prevent ongoing pulmonary damage in pediatric patients who are at risk. 10,11 In particular, no prior studies have examined the gastrointestinal risk factors contributing to bronchiectasis; however, with the development of aerodigestive programs, the role of the gastroenterologist in multidisciplinary care has become more central to the diagnosis and management of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al 3 explore a possible aetiology of bronchiectasis by examining its association with tracheomalacia. Within a historical cohort in a single tertiary paediatric centre, the degree of tracheomalacia, defined while performing a flexible bronchoscopy, was compared in children with or without evidence of bronchiectasis on a conventional high-resolution CT (c-HRCT) image.…”
mentioning
confidence: 99%
“…Although childhood bronchiectasis is still classed as a neglected orphan disease that we know so little about, through efforts such as those of Thomas et al 3 it may not be an orphan for much longer.…”
mentioning
confidence: 99%